Exploring non-bank financial institutions as an alternative means of financingmsmes in Ghana: a case study of Adum-Kumasi. - Ayisi, Alexander (KNUST, 2025)
A Thesis Submitted To The Department Of Accounting And Finance In Partial Fulfilment Of The Requirements For The Degree Of Master Of Business Administration (Finance)